Review of Roger Freitas. 2009. Portrait of a Castrato: Politics, Patronage, and Music in the Life of Atto Melani. New Perspectives in Music History and Criticism. Cambridge and New York: Cambridge University Press - Wilbourne, Emily (Current Musicology, 2009)
Roger Freitas firmly situates his book, Portrait of a Castrato: Politics, Patronage, and Music in the Life of Atto Melani, as biography, yet the text aspires to something more: both the blurb and the introduction promise to clarify ‘what music at this time actually was.’ More properly, Freitas offers an articulate analysis of the social valence of musical performance within the elite circles of the seventeenth-century Italian courts; he focuses on music as a skill with material benefits. The subject of Freitas’s book, Atto Melani (1626-1714), was a castrato, trained as a singer, although eventually he moved away from performance, spending the latter years of his life as a diplomat. According to Freitas, Atto – referred to by his first name, as per contemporary convention – was the ‘most highly documented’ musician of the seventeenth century. With few exceptions, the documents that survive are letters written by Atto, and addressed to a cross-section of the most important political figures in Italy. In his relationship to courtly culture and as a court musician, Atto participated in an increasingly anachronistic model of ‘musical performance,’ one which persisted in contrast with newer, recognizably modern patterns of professionalization associated with the public operatic stage. This is, perhaps, one of the most valuable aspects of this study: Freitas has ably and coherently mapped out the way in which the intricate and asymmetrical obligations of patron and client functioned in seventeenth-century Italy, situating Atto’s musical skills within a broad range of courtly services and deftly portraying the castrato’s gradual shift from court musician to courtier.